PERFORMANCE OPTIMIZATION OF THE CORRUPTION UNIT IN HANDLING CORRUPTION REALIZE PRECISION LAW ENFORCEMENT IN THE JURISDICTION OF POLICE RESORT SUKOHARJO - JANOSLAN HUBERT SINAGA (Advances in Police Science Research Journal, 2022)
This research is motivated by the rampant corruption in the district of Sukoharjo, where the corruption that occurs is mostly about the misuse of village funds. In 2018,2019, and 2020, four cases of corruption in village funds were found. The cOrruption unit that has handled corruption in the last five years has only been able to Resolve so optimization efforts are needed. The purpose of this study s to find out the performance of the corruption unit in handling corruption cases. Including the factors that affect the handling of corruption.. This research uses a qualitative approach with case study research. The focus of this research is on optimizing the performance of the corruption unit in handling corruption crime in the jurisdiction of Sukoharjo Police Station. In collecting data through interviews, observation, and document studies which were analyzed by reducing data, presenting data, then drawing conclusions also verifying data. The knives of analysis in this research are the theory of competence, the theory of management (POAC), the concept of optimization, the concept of performance, the concept of precision, and the concept of law enforcement. The result of this research shows that both the performance and efforts in optimizing the Corruption Unit in handling corruption crime in the jurisdiction of Sukoharjo Police Station were declared not optimal. The problem-solving steps taken are related to increasing the competence of members and improving management in the corruption unit. Suggestions based on this research are, to increase the human resources in terms of member competence and improve the management of the Corruption Unit in handling corruption crime.